Impact of immigration on drug resistance to Mycobacterium tuberculosis in Castellon (Spain): 1995-2003 - Tirado Balaguer, María Dolores; Moreno Muñoz, Rosario; Marín Royo, Margarita; González Morán, Francisco; Pardo Serrano, Francisco; García del Busto Remón, Alfonso; Prada Alfaro, Pablo (Medicina clínica, 2006)
The aim of this study was to know the frequency of resistant Mycobacterium tuberculosis in the province of Castellon (Spain) and to determine whether immigration is associated with resistance. All culture-positive cases diagnosed in Castellon from January 1995 to December 2003 were included in this retrospective study. Susceptibility tests were performed using the Canetti's proportion method and the MB/BacT system. Risk factors associated with tuberculosis were investigated in every case. Six hundred and forty-four cases of tuberculosis were studied: 560 were Spaniards and 84 foreigners. The overall frequency of resistant strains was 5%. The total rate of resistance in Spaniards was 3.7% and in foreigners 13.1%. In Spanish new cases, drug resistance was 3.2% and in foreigners new cases it was 13.9%. In previously treated cases, drug resistance was 6.7% in Spaniards and 0% in immigrants. No acquired drug resistance was detected in immigrants. Of those strains with resistance, 71.9% had resistance to only one drug, 18.7% to two drugs and 9.4% to more than two drugs. Multidrug-resistance was found in 9.4% of the resistant cases, and in 0.5% of all the studied population. The presence of resistant Mycobacterium tuberculosis was associated with the fact of having a foreign nationality (OR = 3.87; p < 0.001). Tuberculosis has been diminishing in Spanish patients in Castellon. Nevertheless, there is an important increase in the number of cases in foreigners, which is associated with a major percentage of resistances. Epidemiological vigilance efforts should especially concentrate on this group in order to support the progressive declivity of the disease.